2017
DOI: 10.3390/molecules22030437
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Induces Apoptosis of Human Osteosarcoma U-2 OS Cells through Endoplasmic Reticulum Stress, Caspase- and Mitochondria-Dependent Signaling Pathways

Abstract: Bone cancer is one of the cancer-related diseases, and there are increased numbers of patients with bone cancer worldwide. Therefore the efficacy of treatment of bone cancer is considered extremely vital. Bufalin has been showed to have biological activities including anticancer activities in vitro and in vivo. However, the exact associated mechanisms for bufalin induced apoptosis in human bone cancer cells are still unclear. In the present study, we investigated the effect of bufalin on the cytotoxic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 59 publications
(79 reference statements)
1
40
0
Order By: Relevance
“…Bufalin has biological activities including inducing cancer cell apoptosis (11)(12)(13)(14)(15)(16)(17) and DNA damage in NCI-H460 human lung cancer cells (18). Recently, we also found that bufalin significantly inhibits cell adhesion, migration and invasion of gefitinib-resistant NCI-H460 cells (19) and induced apoptosis of U-2 OS human osteosarcoma cells (20) and SCC 4 human tongue cancer cells (21).…”
mentioning
confidence: 94%
“…Bufalin has biological activities including inducing cancer cell apoptosis (11)(12)(13)(14)(15)(16)(17) and DNA damage in NCI-H460 human lung cancer cells (18). Recently, we also found that bufalin significantly inhibits cell adhesion, migration and invasion of gefitinib-resistant NCI-H460 cells (19) and induced apoptosis of U-2 OS human osteosarcoma cells (20) and SCC 4 human tongue cancer cells (21).…”
mentioning
confidence: 94%
“…Caspase are hydrolysis enzymes which play an important role in apoptotic cell death. Many studies shown that induction of caspase protein could trigger apoptosis in cancer cells . Therefore, it is estimated that some key biomarkers like caspase‐3, ‐7, and ‐8 can prove if MHA could induce caspase‐dependent cell death.…”
Section: Resultsmentioning
confidence: 99%
“…It is a bufanolide steroid compound. The broad spectrum of anticancer activities of BUF has received considerable attention [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of bufalin-induced cell death comprise its (i) influence on the expression of apoptosis-related genes, (ii) inhibition of tumor cell proliferation, (iii) generation of reactive oxygen species, (iv) endoplasmic reticulum stress, (v) JNK (c-Jun N-terminal kinase) activation, (vi) protein kinase modulating effect, (vii) caspase-and mitochondria-dependent signaling pathways, and (viii) cell cycle arrest via the c-Myc/NF-kappa B pathway [26][27][28][29][30][31][32][33][34][35][36][37]. Despite that BUF is considered as a promising antitumor agent, its poor water solubility, high cardiac toxicity, short circulation half-life and narrow therapeutic window have limited the clinical application of the drug [26].…”
Section: Introductionmentioning
confidence: 99%